Impact of smoking status on early and late outcomes after isolated aortic valve replacement surgery - Saxena, A.; Shan, L.; Dinh, D.; Smith, J.; Shardey, G.; Reid, Christopher; Newcomb, A. (2013)
Background and aim of the study: Currently, insufficient data exist relating to the impact of smoking status on outcomes after isolated aortic valve replacement (AVR) surgery. Methods: Data obtained prospectively between June 2001 and December 2009 by the Australian and New Zealand Society of Cardiac and Thoracic Surgeons (SCTS) Cardiac Surgery Database Program was analyzed retrospectively. Demographic and operative data were compared between patients who were non-smokers, previous smokers and current smokers, using chi-square and t-tests. The independent impact of smoking status on 14 shortterm complications and long-term mortality was determined using binary logistic and Cox regression, respectively. Results: Isolated AVR surgery was performed in 2,790 patients; smoking status was recorded in 2,784 cases (99.8%). Of these patients 1,346 (48.3%) had no previous smoking history, 1,232 (44.3%) were previous smokers, and 206 (7.4%) were current smokers. The 30-day mortality rate was 2.3% in nonsmokers, 2.7% in previous smokers, and 0.5% in current smokers (p = NS). The incidence of perioperative complications was generally similar in the three groups, but current smokers were at an increased risk of pneumonia (p = 0.030) and postoperative myocardila infarction (p = 0.007). The mean follow up period for the study was 37 months (range: 0-105 months). After adjusting for differences in patient variables, the incidence of late mortality was not higher in previous smokers (HR 1.13; 95% Cl 0.87-1.46; p = 0.372) or current smokers (HR 1.25; 95% Cl 0.66-2.36; p = 0.494) compared to non-smokers. Conclusion: Smoking status does not necessarily portend a poorer perioperative outcome in patients undergoing isolated AVR. © Copyright by ICR Publishers 2013.